2018
DOI: 10.1353/hpu.2018.0109
|View full text |Cite
|
Sign up to set email alerts
|

Does Medicaid Coverage Modify the Relationship between Glycemic Status and Teeth Present in Older Adults?

Abstract: Understanding the relationships among diabetes, teeth present, and dental insurance is essential to improving primary and oral health care. Participants were older adults who attended senior centers in northern Manhattan (New York, N.Y.). Sociodemographic, health, and health care information were obtained via intake interviews, number of teeth present via clinical dental examinations, and glycemic status via measurement of glycosylated hemoglobin (HbA1c). Complete data on dental insurance coverage status for 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 42 publications
0
9
0
3
Order By: Relevance
“…One study reported a relationship between tooth loss and chronic kidney disease, especially among older women [ 72 ]. Older adults with < 20 teeth had significantly increased risk of metabolic syndrome, higher serum lipid peroxide, and glycemic status [ 73 75 ]. However, the relationship was reversed in a study population of Medicaid patients for glycemic status [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a relationship between tooth loss and chronic kidney disease, especially among older women [ 72 ]. Older adults with < 20 teeth had significantly increased risk of metabolic syndrome, higher serum lipid peroxide, and glycemic status [ 73 75 ]. However, the relationship was reversed in a study population of Medicaid patients for glycemic status [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, severe cognitive impairment or a reduced mental status was associated with being edentulous [ 44 , 45 ]. Edentulous subjects also had significantly increased risk of metabolic syndrome, higher serum lipid peroxide, and glycemic status [ 73 75 ], and Yamamoto and colleagues reported an association between edentulism and incident depressive symptoms [ 120 ]. While it may not be surprising that complete edentulism is associated with greater odds of self-rated “fair/poor” health in older diabetics, who also experienced additional physically unhealthy days in the past 30 days, it is also notable that the loss of any permanent teeth was also associated with these findings [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…In concert with the public health perspective of this review, the present model was adapted from an ecological model on health behavior and education (120) and based on an analysis of findings from systematic reviews of cardiovascular disease and cancer disparities (28,36,56,57,94). Nevertheless, it has also proved useful in contextualizing multilevel influences on oral health disparities, their intervention targets, and the key stakeholders and outcomes that are affected by the devised interventions (44,58,(97)(98)(99)(100)102).…”
Section: Separate Systems Of Oral Health and Medical Care Provisionmentioning
confidence: 99%
“…The life course approach is the study of long-term effects on chronic disease risk of physical and social exposures during gestation, childhood, adolescence, young adulthood, and later adult life (14). In disadvantaged populations and underserved communities, oral disease risk is elevated throughout the life course owing to, e.g., socioeconomic status, discrimination, and lack of eligibility and/or high out-of-pocket costs for public and private insurance coverage (9,12,19,97,99,116). In particular, exposures that are patterned by social factors include poor nutrition, lack of preventive primary and oral health care (including vaccination against HPV), inferior quality of restorative oral health care (31,34), violence and injury leading to face trauma, and excessive alcohol and tobacco use, all of which may affect teeth and their supporting structures, leading to dental caries (beginning in early childhood), oropharyngeal cancer (currently an epidemic among younger men), periodontal disease (highly prevalent with increasing age), oral cancers (especially in older men), and eventually root caries and tooth loss (particularly in older adults).…”
Section: Life Course Perspective On Oral Health Promotionmentioning
confidence: 99%
“…Very recent papers underscore that lack of adequate and consistent funding through Medicare and Medicaid continues to persist regarding the provision of oral health care for the U.S. geriatric population (Northridge et al, 2018;Wakgama et al, 2018). One states that Medicare, the U.S. federal public insurance program for older adults, virtually still "does not include dental insurance coverage, and Medicaid (a public insurance program for the economically disadvantaged and disabled persons) has variable and often limited dental insurance coverage for adults on a state-bystate basis" (Northridge et al, 2018). Another recent paper states the nation's Medicaid state-by-state patchwork quilt of dental care coverage "borders on nonsensical" for this especially vulnerable geriatric LTC population (Wakgama et al, 2018).…”
Section: Discussionmentioning
confidence: 99%